Counselor’s Role in Managing Learning Loss in The Post-Pandemic Period - Tiara Wulandari; Amirah Diniaty; Amalia Madihie (Program Studi BKPI IAIN Salatiga, 2022)
This study aims to depict the counselors' understanding of senior high school students’ learning loss and their role in handling student learning loss. Applying descriptive qualitative study, this study involves four counselors, two homeroom teachers, and six students experiencing learning loss. The data were collected through interviews and analyzed descriptively. The study found that the counselors understood that the students experienced learning loss, indicated by decrease in their academic achievement, was caused by their lack of autonomous learning, internet connection issues, and lack of learning motivation. To address this issue, counselors attempted to motivate their students, invited them to an individual counseling session, and collaborated with homeroom teachers.